A New Approach to Preanesthetic Site Verification After 2 Cases of Wrong Site Peripheral Nerve Blocks. Issue 2 (1st February 2008) - Stanton, Maureen A.; Tong-Ngork, Sarani; Liguori, Gregory A.; Edmonds, Chris R.
Abstract : Objective: We discuss the importance of a "preanesthetic site verification" and highlight 2 significant modifications to a policy developed at our institution in 2003. Case Report: The report describes 2 cases of wrong site peripheral nerve blocks that initiated protocol amendments to address shortcomings of the original policy. Two specific limitations were identified to improve upon. First, the practitioner must not overlook the site verification as it is essential prior to every block. Second, time delays between the verification and block performance should be minimized. Conclusions: The "preanesthetic site verification" is an integral part of preventing wrong site block and surgery. To ensure that it is carried out before every peripheral nerve block, a unique multidisciplinary approach was adopted in which the block needles were removed from anesthesia carts and transferred to a separate container in the area of the circulating nurse. The anesthesiologist must now request a block needle from the circulating nurse immediately prior to block performance and confirm the site at that time. This safety process emulates the presurgical site verification that takes place before a scalpel is passed to a surgeon. Furthermore, the circulating nurse must remain at the bedside until block initiation to make sure that delays between site verification and block performance do not impinge on correct site placement.